(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2023)
This work deals with 252 terracottas standing out because of the high percentage of heads broken at the neck and of female figures which have been seized in seventies of the last century. The variety of iconographical depictions detected ranges from the archaic types to the widespread Tanagras, providing some instances of craftsmen attempting to diversify standardized iconographies and to optimize the productive resources. Parallels point out the provenance of terracottas from Taranto and allow us to find precise correspondance between the figurines yielded by a few sacred contexts of the city and ours. Due to their votive function and its connection with the cult practice of fragmenting offerings, objects even if they are out of context may contribute, to some extent, to the archaeology of ritual in Magna Graecia.